Detecting Risk Factors of Road Work Zone Crashes from the Information Provided in Police Crash Reports: The Case Study of Portugal - Santos, Bertha (2021)
Submitted by SANTOS (bsantos@ubi.pt) on 2021-02-11T12:29:06Z No. of bitstreams: 1 safety-07-00012.pdf: 509038 bytes, checksum: fb6adf62ed9cee4e19b29deede0cf557 (MD5)